Pembelajaran dengan Media Sicota untuk Meningkatkan Hasil Belajar Matematika - Mal Alfahnum; Maya Masitha Astriani (Journal on Education, 2024)
The application of Sicota learning devices when learning helps students overcome problems and create learning situations according to their needs, making participants active and motivated so as to increase the success and accuracy of the learning process, the quality of learning, and mathematics learning outcomes. This study aims to help improve student learning outcomes in mathematics subjects on special angle trigonometry material, at SMAN 85 Jakarta Class XI Sample 32 Students. The research approach is quantitative pre-experimental (one group pretest - post test design). The research participants were only one group that underwent the pre-test, treatment, and post-test. The success or failure of the treatment was determined by the difference in the results of the pre-test and post-test. The multiple-choice test tool consisted of 20 questions. Data were analyzed using normality test techniques and t-tests. Only 2 students (6%) completed the pretest, but this number increased to 29 (91%) after the posttest, resulting in an increase in mathematics achievement of 84%. The number of students who did not complete the pretest was 30 (94%), but after the posttest was carried out, this number decreased to 3 (9%), resulting in a decrease in value of 84%. The difference in students' mathematics learning outcomes in the pre-test and post-test was very significant, namely 84%, this shows that the Sicota learning media is effective in improving mathematics learning outcomes in the special angle trigonometry material.